The home advantage in sport competitions: Courneya and Carron's (1992) conceptual framework a decade later - Carron, A. V.; Loughead, T. M.; Bray, S. R. (Journal of Sports Sciences, 2005)
This paper had three aims. The first was to review research carried out on the home advantage from 1992 to the present. The second was to examine the extent to which a conceptual framework proposed by Courneya and Carron (1992) was/is viable as a tool to highlight and organize an understanding of the home advantage. The final aim was to provide suggestions for future research.